البعد الهوياتي في العلاقات الأورو متوسطية: تقارب متوسطي أم هيمنة ثقافية - بلاغماس اسماء (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2021)
مع نهاية الحرب الباردة، شهدت السياسات الأوروبية تجاه دول جنوب المتوسط تحولات مهمة في اتجاه مزيد من الاهتمام بالمتغيرات الاقتصادية والثقافية، وتعمق هذا التوجه بخاصة في الفترة التي تلت مؤتمر برشلونة، لكن وبفعل تزايد موجات الهجرة وتنامي العمليات الإرهابية ومعها الإسلاموفوبيا، فقد دفعت هذه التطورات بالأبعاد الهوياتية والثقافية إلى ممارسة تأثير أكبر في أجندة الاتحاد الأوربي تجاه المتوسط، ويهتم هذا المقال بفحص ما إذا كان اهتمام الاتحاد الأوروبي بالبعد الهوياتي الثقافي في علاقاته الأورو متوسطية رغبة في تحقيق التقارب المتوسطي أم أنه مهتم فعليا بتحقيق الهيمنة الثقافية ؟ وقد توصلت إلى أن بلدان الاتحاد الأوربي تعمد إلى توظيف المتغير الثقافي لإرساء مزيد من الهيمنة متعددة الأبعاد. الكلمات المفتاحية: الهوية؛ الهوية الثقافية؛ الإرهاب؛ الهجرة؛ الحوار الثقافي. Abdtract: By the end of the Cold War, European policies towards southern Mediterranean countries have became more and more economic and cultural oriented, these policy trends have gotten momentum following the Barcelona Conference, but due to the increasing waves of immigration and the growth of terrorist operations along with Islamophobia, these developments increased the importance of Identity and cultural dimensions. This article examines whether the European Union’s interest in the cultural identity dimension in its Euro-Mediterranean relations has the intention of achieving a Mediterranean rapprochement, or is it actually interested only in achieving cultural hegemony over its Mediterranean sphere of influence? I found that EU countries are actually using identity/cultural issues to realize a multidimensional hegemony. Keywords: Identity; Cultural identity; Terrorism; Immigration; Cultural Dialogue